Minimally invasive surgery versus sternotomy in native mitral valve endocarditis: a matched comparison. (18th August 2021) - Kofler, Markus; Van Praet, Karel M; Schambach, Julie; Akansel, Serdar; Sündermann, Simon; Schönrath, Felix; Jacobs, Stephan; Falk, Volkmar; Kempfert, Jörg
Abstract:  : OBJECTIVES: The present study compared the clinical outcomes between minimally invasive surgery (MIS) and median sternotomy (MS) in patients with native mitral valve infective endocarditis. METHODS: From 2009 to 2019, a total of 154 patients with acute ( n  = 131, 85%) or subacute ( n  = 23, 15%) native mitral valve infective endocarditis were included in the study. One-to-one nearest neighbour propensity score matching considering endocarditis severity using the dedicated De Feo score and 19 other clinically relevant baseline variables resulted in a population of 39 matched pairs. The matched cohort was investigated regarding operative and postoperative outcomes. RESULTS: Both groups showed similar results regarding cardiopulmonary bypass time [MIS: 96 min (77–138), MS: 99 min (88–127); P  = 0.780] and aortic cross-clamp time [MIS: 64 min (54–90), MS: 65 min (59–83); P  = 0.563], whereas overall operative time was shorter through minimally invasive access [MIS: 138 min (112–196), MS: 187 min (175–230); P  = 0.005]. Although the rate of revision for bleeding was similar in both groups [MIS: 12.8% ( n  = 5), MS: 10.3% ( n  = 4); P  = 1.000], MIS was associated with fewer red blood cell unit transfusions [MIS: 1 unit (0–4), MS: 4 units (2–10); P  = 0.001] and fewer fresh frozen plasma unit transfusions [MIS: 0 units (0–0), MS: 1 unit (0–5); P  = 0.002]. MIS was associated with a shorter ventilation time [MIS: 708 min (429–1236), MS: 1440 min (659–4411); P  = 0.024] and a lower rate of reintubation after extubation [MIS: 5.1% ( n  = 2), MS: 25.6% ( n  = 10); P  = 0.021]. CONCLUSIONS: In patients suffering from native mitral valve infective endocarditis, MIS provides significant clinical benefits over sternotomy in selected patients. Subject collection: 117, 121. Abstract : Infective endocarditis (IE) represents a serious medical condition that is challenging to diagnose and to treat and is characterized by considerable morbidity and mortality [1, 2].